(untitled) (Indian Journal of Animal Production and Management, 2025)
Toxoplasmosis is a common zoonotic infection caused by the protozoan parasite Toxoplasma gondii. It represents a significant public health concern worldwide. Early and accurate diagnosis is essential, especially among immunocompromised patients and pregnant women.This meta-analysis systematically reviews peer-reviewed studies (2015–2025) to evaluate molecular diagnostic methods used for detecting T. gondii in humans and animals.Data were extracted and synthesized from recent studies focusing on molecular detection techniques, methodological differences, diagnostic accuracy, and prevalence rates. Special attention was given to polymerase chain reaction (PCR) and its variants due to their superior sensitivity and specificity compared to conventional serological assays.PCR-based assays targeting multicopy nucleotide sequences such as B1 and 18S rDNA demonstrated higher sensitivity and specificity.Pooled prevalence varied by host species and geographical region.Emerging methods including loop-mediated isothermal amplification (LAMP) and real-time PCR (qPCR) were identified as rapid and quantitative approaches with strong diagnostic potential.Molecular diagnostic methods offer significant advantages for detecting T. gondii, but variability in protocols affects reliability. The study emphasizes the need for standardized and harmonized diagnostic procedures to achieve optimal outcomes in toxoplasmosis detection, management, and control.